OPTIMALISASI PENGHIMPUNAN ZAKAT MELALUI DIGITAL FUNDRAISING - Ade Nur Rohim (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
The developments in zakah management is considered increasingly important along towards the digital era. Based on studies in the performance of several LAZs carried out, the realization of zakah collection is currently far from the potential of zakah which should be, so LAZ needs to take progressive steps in the implementation of the digitization system. This article aims to reveal the challenges faced by LAZ in the dissemination and collection of zakah in digital era, complete with the obstacles faced. In addition, it was stated about the form of strategy for utilizing digital fundraising channels, such as: websites, email marketing, search engine marketing, social media marketing, and social networks, in order to conduct more optimal zakah collection. This research is a qualitative research, using a literature study approach. Data collected related to the research were taken from several literary sources including scientific journals, several books, and related articles published in online media. As a result, by transforming into the use of canals on digital fundraising, zakah management and collection programs can be carried out better while also educate the public about the obligation for zakah.